Experiences of Infection Prevention and Control Nurses (IPCNs) in performing their roles and duties in the Indonesia Army Central Hospital: A qualitative descriptive study - Laurentia Dewi; Achir Yani S. Hamid; Rita Sekarsari (Belitung Raya Foundation, Indonesia, 2023)
Background: The Infection Prevention and Control Nurse (IPCN) is a professional nurse with a crucial role in promoting patient safety and service quality by preventing and controlling infections. However, little is known about their experiences regarding their roles and duties, particularly in Indonesia. Objective: This study aimed to explore IPCNs’ experiences in performing their roles and responsibilities, including motivations and obstacles encountered, as well as organizational support while carrying out their jobs. Methods: This research used a qualitative descriptive study design, collecting data through Focus Group Discussions (FGDs) with six purposively sampled participants in April 2021 at the Gatot Soebroto Army Central Hospital (RSPAD), Jakarta, Indonesia. Thematic analysis was used to analyze the data. Results: Five themes were identified: 1) roles and duties of IPCNs, 2) conducive work environment, 3) constraints in carrying out tasks, 4) management support, and 5) hopes. Conclusion: This study provides new insights into IPCN roles and duties that require collaboration and coordination with multiple professions, as well as management support to overcome obstacles that hinder fulfilling tasks and hopes of improving IPCN performance according to competency-based career paths to achieve patient safety, service quality, and job satisfaction.